A Rapid Micropropagation of nodal explants of Eclipta alba (L.); A Multipurpose Medicinal Herb - Devaraj, Natarajan; Ragavendran, C; Kamalanathan, D (Research in Biotechnology, 2014)
An efficient in vitro regeneration protocol was developed for medicinally important plant Eclipta alba. Successful regeneration and multiplication of nodal explants of E. alba were obtained in cytokinin enriched B5 medium. Several cytokinins [6-benzylaminopurine (BAP), kinetin (KIN), thidiazuron (TDZ), gibberellic acid (GA3) and spermidine] were supplemented alone and its combinations for obtaining better results. The best growth frequency response was achieved in the combinations of 1.0 BAP + 0.3 KIN + 1.5 GA3 (mg/L) concentration (7.4 ± 0.9 cm shoot length & 100 % regeneration). Better roots were developed in half-strength B5 medium along with IBA (1.0 mg/L) hormone and exhibits maximum root length (7.0 ± 0.8cm) along with multiple roots (8.8 ± 0.8) at 92 %. The well-developed Plantlets were successfully acclimatized to plastic-cups containing autoclaved sand and garden soil (1:1) and kept undisturbed with plastic cover for maintaining the humidity. The plantlets were watered regularly and maintained at green house.